Surface modification of poly-E-caprolactone electrospun fibrous scaffolds using plasma discharge with sputter deposition of a titanium target - Barbarash L. S. Leonid Semenovich; Bolbasov E. N. Evgeny Nikolaevich; Antonova L. V. Larisa Valerjevna; Matveeva V. G. Vera Gennadjevna; Velikanova E. A. Elena Anatoljevna; Shesterikov E. V. Evgeny Viktorovich; Anissimov Y. G.; Tverdokhlebov S. I. Sergei Ivanovich (2016, 2016)
Title screen